Faktor-Faktor yang Berhubungan dengan Kejadian Infeksi Saluran Pernafasan Akut (ISPA) pada Balita - Restu, Fadlan Kurnia; Darwel, Darwel; Nur, Erdi; Marza, Firwandri; Hidayanti, Rahmi; Sumihardi, Sumihardi (Jurnal Kesehatan Lingkungan Mandiri, 2025)
In the working area of the Andalas Health Center, ARI (Acute Respiratory Infection) ranked first among the ten most common diseases. As of December 2022, 80.43% of houses in this area did not meet health standards. This study aimed to identify factors associated with the incidence of ARI in toddlers in the Andalas Health Center area in 2023. This was an analytical survey using a cross-sectional approach, conducted from March to June 2023. Data were collected through interviews and home environment assessments. Data analysis was performed using univariate and bivariate methods with the Chi-square test.Results showed that 62.8% of toddlers experienced ARI. Among the assessed homes, 60% had inadequate ventilation, 60% had poor natural lighting, 57.1% had improper room temperature, 68.6% had unsuitable humidity levels, and 54.3% had high occupancy density. Bivariate analysis revealed significant associations between natural lighting (p=0.0001; PR=6.667), room temperature (p=0.0001; PR=4.750), and humidity (p=0.0001; PR=9.625) with ARI incidence. However, no significant relationship was found with ventilation (p=0.353) and occupancy density (p=0.073). It is recommended that sanitarians at the Andalas Health Center increase healthy home education and implement preventive measures, including physical home improvements. Cross-sector collaboration is encouraged to support home renovation programs for low-income families, to create a healthy home environment.